Kesesuaian Alasan Pengajuan Peninjauan Kembali Dalam Tindak Pidana Penipuan Dengan Ketentuan KUHAP - Ismail Eka Syahrial (Verstek, 2017)
This research aims is to find out whether the reason for the submission of a review in supreme court by the convicted person on the ground of novum is in compliance with article 263 paragraph (2) letter a Code Of Criminal Procedure on the basis of the review request as well as to find out whether the legal consideration of Supreme Court Justices grant the petition for review in the case of fraud is in compliance with article 266 Code Of Criminal Procedure regarding the result of the request for review.     Types of legal research this is a normative legal research that is both prescriptive and applied. Type of data used are secondary data. Study document used as data collection techniques.      The results obtained from the research are : first, the reason for filing the review by Widar Kusuma convict on fraud lawsuit on the basis of novum has pursuant to section 263 subsection (2) letter a Code Of Criminal Procedure on the basis of a request for review. Second, consideration of the law of the Supreme Court Justices grant the petition for review in the case of fraud on a Supreme Court Verdict Number 36/PK/Pid/2013 have been in accordance with the article 266 Code Of Criminal Procedure regarding the result of the request for review, namely the suspension of the verdict of the District Court and the deliverance of the convicted person.      Keywords : The Basis Of The Review Request, Novum, The Case Of Fraud, Legal Consideration Of Supreme Court Justices